2022
DOI: 10.3390/jcm11226606
|View full text |Cite
|
Sign up to set email alerts
|

Thickness of Biceps and Quadriceps Femoris Muscle Measured Using Point-of-Care Ultrasound as a Representation of Total Skeletal Muscle Mass

Abstract: Generalized loss of muscle mass is associated with increased morbidity and mortality in patients with cancer. The gold standard to measure muscle mass is by using computed tomography (CT). However, the aim of this prospective observational cohort study was to determine whether point-of-care ultrasound (POCUS) could be an easy-to-use, bedside measurement alternative to evaluate muscle status. Patients scheduled for major abdominal cancer surgery with a recent preoperative CT scan available were included. POCUS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…To assess skeletal muscle status, the cross-section (anterior-posterior diameter) of the musculus biceps brachii, rectus femoris and vastus intermedius will be measured bilaterally with a handheld ultrasound system (Philips FUS6882 Lumify L12-4, Philips, Eindhoven, the Netherlands). 37 Patients will be positioned in a supine position to acquire full muscle relaxation. Subsequently, Open access the transducer will be placed perpendicular to the long axis of the muscles.…”
Section: Sarcopeniamentioning
confidence: 99%
“…To assess skeletal muscle status, the cross-section (anterior-posterior diameter) of the musculus biceps brachii, rectus femoris and vastus intermedius will be measured bilaterally with a handheld ultrasound system (Philips FUS6882 Lumify L12-4, Philips, Eindhoven, the Netherlands). 37 Patients will be positioned in a supine position to acquire full muscle relaxation. Subsequently, Open access the transducer will be placed perpendicular to the long axis of the muscles.…”
Section: Sarcopeniamentioning
confidence: 99%
“…Recent research revealed a statistically significant link between muscle strength and the thickness of the biceps brachii, rectus femoris, and vastus intermedius measured using POCUS [ 23 , 24 ]. A previous study showed that ultrasounds could help shorten the time to diagnosing sarcopenia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early detection of muscle changes is necessary for appropriate management of rehabilitation strategies 7 , 16 , but volitional tests are not applicable in this acute disease phase 17 , 18 . Nonvolitional assessment tools such as computed tomography and magnetic resonance imaging and invasive techniques such as biopsy, electromyography and nerve conduction studies are highly accurate for the diagnosis of muscle changes; however, these resources are limited in this specialized COVID-19 ICU scenario because of high cost, radiation exposure, and aerosol transmission-related health hazards 18 21 .…”
Section: Introductionmentioning
confidence: 99%